KEMAMPUAN ADAPTASI MASYARAKAT PESISIR MENGHADAPI DAMPAK BAHAYA ABRASI AKIBAT BANJIR ROB DAN PERUBAHAN IKLIM (STUDI KASUS: PERUBAHAN DESA BEDONO SAYUNG DEMAK KURUN WAKTU TAHUN 1990-2020) - Ns Aries Susanto; Eko Teguh Paripurno; RR. Susilastuti Dwi Nugrahajati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Coastal areas along the northern coast of Java are highly vulnerable to the impacts of climate change, particularly coastal abrasion, tidal flooding, and land subsidence. Bedono Village, Sayung Sub-district, Demak Regency, represents an extreme case of a coastal community experiencing profound socio-ecological transformation due to cumulative and progressive environmental pressures. This study aims to analyze the existing hazard conditions, forms of community adaptation, and adaptation strategies perceived as resilient by local communities in responding to coastal abrasion and tidal flooding during the period 1990-2020. A qualitative research approach was employed, utilizing in-depth interviews, focus group discussions, field observations, and document analysis. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that abrasion, tidal flooding, and land subsidence have resulted in land loss, infrastructure damage, livelihood shifts, and coastal ecosystem degradation. Despite these challenges, the community of Bedono Village has demonstrated strong adaptive capacity through physical, economic, socio-cultural, and ecosystem-based adaptation strategies. Resilient adaptation is characterized by participatory, sustainable, and context-specific practices that integrate local knowledge, such as mangrove rehabilitation, stilt houses, livelihood diversification, and strengthened community institutions. These findings highlight the crucial role of community-based adaptation as a foundation for climate change adaptation policies in vulnerable coastal regions